Advancements and Future Directions in Thermal Barrier Coatings: A Comprehensive Review - Parthiban, Karthiga; Mukhopadhyay, Anoop Kumar; Ghosh, Sumana (Chemical and Materials Sciences: Developments and Innovations Vol. 8, 2024)
Thermal barrier coatings (TBCs) protect engine parts of aircraft and industrial gas turbines. TBC system is a complex structure comprising several metal and ceramic-based layers. The structure as well as composition of TBCs determine their properties during actual applications. TBCs are usually prepared by the atmospheric plasma spraying method, which is more cost-effective than other techniques. Bilayered, multilayered and functionally graded TBCs have been proposed by the researchers to achieve enhanced coating performance. The current review paper is focused on the state of the art of recent TBC materials, design and fabrication techniques. Attempt has also been made to make a comparative study on existing TBC materials. Future perspectives have been put forward based on the present status.